Challenges of Improving Teachers’ Assessment Practices - Shamatov, Duishon (Journal of Research and Reflections in Education, 2007)
This article reports the outcomes of a qualitative case study which explored how school teachers develop their assessment while attending an in-service teacher education programme. Semi-structured interviews and document analysis were two methods used to explore the Master of Education students at Aga Khan University Institute for Educational Development (AKU-IED). These students come from developing countries in Central Asia, South Asia and East Africa. Prior to joining AKU-IED, most of these students have had experienced assessment practices characterized in my study as ‘traditional’, teaching and learning have been geared towards examinations and tests. The selective purpose of assessment selects and rejects people, and social reproduction is maintained by the traditional assessment. Additionally, traditional assessment has often caused great deal of psychological discomfort and elements of ‘unproductive competition’ reflecting on extrinsic reward in schooling. At AKU-IED, the M.Ed. students have a very intensive transformative learning experience. They are encouraged to critically examine their existing educational philosophy, including assessment notions. As a result, many students re-modify their assessment theories and practices. After the completion of the M.Ed. program the students are potentially in a position where they are able to influence assessment practices, to varying degree, when they return to their home work environments.
Keywords: qualitative approach; paradigm shift; assessment practices; reconceptualization; change